Genotype by environment interaction of nine cotton varieties for inter Andean Valleys in Colombia: Evaluation of cotton genotypes in different environments - Mejia-Salazar, Julian Roberto; Galeano-Mendoza, Carlos Hernando; Burbano-Erazo, Esteban; Vallejo-Cabrera, Franco Alirio; Arango, Miguel (Agronomía Mesoamericana, 2020)
Introduction. The use of stability estimators for agronomic characteristics of interest allows understanding the behavior of the genotype in relation to those environmental factors that influence its expression. Objective. The objective of this study was to determine genotype by environment (GE) interaction to select cotton varieties with a high seed yield potential and fiber percentage. Materials and methods. Nine varieties of transgenic cotton were evaluated in ten localities distributed in two geographically different ecoregions: geographical valleys of the Magdalena and Cauca rivers, by means of random complete block design, between the months of March and August in 2013. Results. Cotton seed yield had significant GE interaction, where the three principal components (PC) of the Additive Main Effects and Multiplicative Interaction (AMMI) model were significant (p<0.01), with contributions of 86.9, 6.4, and 3.3 %, respectively. The average yield for the two ecoregions were 3.3 t ha-1 (Magdalena river geographical valley) 4.5 t ha-1 (Cauca river geographical valley), and for all the evaluated localities in the ecoregions was 3.9 t ha-1. Fiber percentage did not present significative GE interaction and had an average value of 43,34%. The V004 variety showed the best performance with an average yield of 4.9 t ha-1. The varieties with greater adaptability were V001 and V002. A high correlation was observed between the most productive varieties and the most productive environments. Conclusion. The differential behavior between varieties and localities for yield allowed to select varieties for specific environments, or with phenotypic plasticity for several environments.